ANALISIS TEGANGAN PISAU PENCACAH LIMBAH KAKAO DENGAN METODE BEDA HINGGA - Fahriansyah Fahriansyah (Jurnal Rekayasa Mesin, 2022)
One of the vital components of a crushing machine is a crushing blade. Where the crusher blade works and is in direct contact with the cocoa waste to be crushed. Many crushing blades wear out quickly after being used for a short time because the blade material has low strength.The aim of this study was to analyze the blade in the crusher machine used by farmers to handling cocoa waste. The blade usings material of steel by utilizing waste car spring sheets with ASTM A29 steel type which is formed into a crusher blade because the price is cheap and easy to obtain. 3-D finite element design and analysis were carried out using Solidwork software. The blade is given a load variation from 100N - 1000N to determine the value of stress, deformation, and safety factor. The results of the simulation and analysis on the crusher blade show a downward trend starting at a load of 400 N, where the stress is 444,738 N/mm2, the maximum shape change is 3.48066 mm, and the safety factor seems to be low in the red distribution with FOS below 1, which is 0.989347.